ANALISIS SWOT MANAJEMEN KOLEKSI UNTUK SISWA BERKEBUTUHAN KHUSUS DI PERPUSTAKAAN SEKOLAH - Elvaretta Vito Dhinosa; Putri Nurul Faizah; Vita Amelia (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2024)
This research focuses on collection management in the Elok Bertuah Library of SLB Negeri Pembina Pekanbaru, aiming to support students with special needs by providing inclusive information resources. In this endeavor, the SWOT analysis method was used to evaluate strengths, weaknesses, opportunities, and threats in the library's collection management. The findings show that the library has successfully provided a variety of relevant collections, such as braille books and braille Qur'an, which are very beneficial for visually impaired students. However, the research also found weaknesses in terms of inadequate storage facilities as well as a suboptimal cataloging system, which can limit students' accessibility to existing collections. Opportunities to improve collection management are seen through collaboration with inclusive education institutions and the utilization of government grants for further development. The implementation of appropriate strategies is expected to improve the accessibility of the collection and the quality of services to support the inclusive learning process and ensure that every student with special needs has equal access to information. Through this research, it is hoped that useful strategic insights can be generated for libraries in improving service quality and collection accessibility to support inclusive education sustainably.